Molecular systematics of Caryopteris (Lamiaceae) and its allies with reference to the molecular phylogeny of subfamily Ajugoideae. Issue 2 (23rd February 2018) - Xiang, Chun-Lei; Zhao, Fei; Cantino, Philip D.; Drew, Bryan T.; Li, Bo; Liu, En-De; Soltis, Douglas E.; Soltis, Pamela S.; Peng, Hua
Abstract: Ajugoideae, the third–largest subfamily of Lamiaceae with 23 genera and about 760 species, is distributed worldwide, but is primarily found in tropical regions. During the past two decades, substantial progress has been made towards discerning phylogenetic relationships and generic boundaries in Ajugoideae, but major questions still remain. This phylogenetic study was conducted using 422 DNA sequences from seven DNA regions (nrITS, ETS, and matK, rbcL, rps16, trnL–trnF, trnH–psbA) representing 50 species from 22 of 23 genera in Ajugoideae, to reconstruct the backbone phylogeny of the subfamily, with emphasis on phylogenetic relationships among Caryopteris, Schnabelia and their closest allies. Key results: (1) Ajugoideae is monophyletic and can be divided into four main clades. (2) Discretitheca and Glossocarya, which have not been included in any previous molecular analysis, are members of Ajugoideae and closely related to Karomia and Rotheca. (3) Expanded Schnabelia is monophyletic, sister to Rubiteucris, and consists of two morphologically distinct clades, recognized here as sect. Cylindricaulis and sect. Schnabelia. (4) Traditionally defined Caryopteris is confirmed to be polyphyletic, with several segregate genera. (5) Recircumscribed Caryopteris was found to be monophyletic, but intrageneric relationships were not fully resolved. Synapomorphies of Caryopteris include boat–shaped nutlets that are winged along the edge, fimbriate anterior corolla lobes, and suprareticulate pollen sculpturing. Caryopteris forrestii var. minor was elevated to species rank based on molecular and morphological evidence.